Edukasi Apoteker Cilik Terkait Pengenalan Obat Kepada Siswa Kelas 5 SD Negeri Mangkura 1 Makassar - Sri Wahyuningsih (Universitas Mataram, 2021)
Sources of information about drugs are pharmacists, but many people do not know the Pharmacist profession. This is causes problems not only in adults but in children. Lack of knowledge about drugs in children can lead to drug abuse. The purpose of this activity is to educate Young Pharmacists regarding the introduction of drugs and as an embodiment of drug awareness ambassadors from an early age. This activity has been carried out at SD Negeri Mangkura 1 Makassar with 54 participants from 5th-grade elementary school students. The method of implementing the activity begins with educating the pharmacist on delivering the Young Pharmacist material, singing the Young Pharmacist jingle, and continuing with a question and answer session regarding drug knowledge to elementary school students. This Young Pharmacist education activity got positive results for 5th-grade students of SD Negeri Mangkura 1 Makassar which was seen from the increase in student's knowledge about the Pharmacist profession and students were very enthusiastic about giving good choices or bad choices regarding the safety of drug use. In addition, two Young Pharmacist ambassadors were chosen as the embodiment of drug awareness ambassadors from an early age.